Replicable Interprofessional Competency Outcomes from High-Volume, Inter-Institutional, Interprofessional Simulation - Deborah Bambini; Matthew Emery; Margaret de Voest; Lisa Meny; Michael J. Shoemaker (MDPI AG, 2016)
There are significant limitations among the few prior studies that have examined the development and implementation of interprofessional education (IPE) experiences to accommodate a high volume of students from several disciplines and from different institutions. The present study addressed these gaps by seeking to determine the extent to which a single, large, inter-institutional, and IPE simulation event improves student perceptions of the importance and relevance of IPE and simulation as a learning modality, whether there is a difference in students' perceptions among disciplines, and whether the results are reproducible. A total of 290 medical, nursing, pharmacy, and physical therapy students participated in one of two large, inter-institutional, IPE simulation events. Measurements included student perceptions about their simulation experience using the Attitude Towards Teamwork in Training Undergoing Designed Educational Simulation (ATTITUDES) Questionnaire and open-ended questions related to teamwork and communication. Results demonstrated a statistically significant improvement across all ATTITUDES subscales, while time management, role confusion, collaboration, and mutual support emerged as significant themes. Results of the present study indicate that a single IPE simulation event can reproducibly result in significant and educationally meaningful improvements in student perceptions towards teamwork, IPE, and simulation as a learning modality.